2020
DOI: 10.1007/s10433-020-00578-3
|View full text |Cite
|
Sign up to set email alerts
|

Shifting self-perceptions of ageing: differential effects of value priorities on self-perceptions of ageing beyond age stereotypes

Abstract: Self-perceptions of ageing (SPA) are important predictors of health in later life. However, research on antecedents of SPA other than age stereotypes is scarce. To address this gap, this study investigates the impact of personal value priorities beyond age stereotypes on SPA. Can values as the motivational basis of attitudes and evaluations predict gain-and loss-related SPA? To answer this question, we conducted multiple regression analyses of longitudinal data from two waves (2008, 2011) of the German Ageing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Thus, by examining the higher-order factors of agency and communion, our study provides a more general understanding of personality and SPA, which may also be useful to further explore the relationship between the two constructs. Furthermore, our study indicates that agency and communion as fundamental dimensions of personality relate to SPA not only on the level of personal values ( Blawert & Wurm, 2021 ), but also on the level of traits. In addition, our findings add to studies pointing to the role of agency and communion for overall adaptation (i.e., successfully and flexibly meeting situational demands) and well-being in later life by showing that these traits also relate to the way old-old adults perceive their own aging.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, by examining the higher-order factors of agency and communion, our study provides a more general understanding of personality and SPA, which may also be useful to further explore the relationship between the two constructs. Furthermore, our study indicates that agency and communion as fundamental dimensions of personality relate to SPA not only on the level of personal values ( Blawert & Wurm, 2021 ), but also on the level of traits. In addition, our findings add to studies pointing to the role of agency and communion for overall adaptation (i.e., successfully and flexibly meeting situational demands) and well-being in later life by showing that these traits also relate to the way old-old adults perceive their own aging.…”
Section: Discussionmentioning
confidence: 65%
“…While, to our knowledge, associations of SPA with agentic and communal traits have never been examined, we found associations with agentic and communal personal values in an earlier study. Using population-based, longitudinal data of adults aged 40 + from Germany, that study demonstrated that agentic and communal personal values are differentially related to change in SPA domains ( Blawert & Wurm, 2021 ): The growth-related agentic value of openness to change as well as the growth-related communal value of self-transcendence were found to predict increases in SPA related to ongoing development over the course of three years, while self-transcendence additionally predicted decreases in SPA related to social losses during the same period. These findings suggest domain-specific associations of agency and communion with SPA.…”
Section: Personality and Spamentioning
confidence: 99%
“…It has also been noted that an individual's competing demands and values may vary in importance over time due to changing life circumstances and stages of the disease. 32 Indeed, on any one day or week, the patient may experience a range of symptoms that may either prevent them from participating or enable them to participate in these lifestyle choices. When addressing holistic health, culturally informed care can guide further assessment and significantly change treatment recommendations and adoptability.…”
Section: Cultural and Diversity Considerations In Wellnessmentioning
confidence: 99%